"Tying your ngemb": Negotiating identity in Senegalese wrestling. (September 2021) - Hann, Mark; Chevé, Dominique; Wane, Cheikh T
More than merely a combat sport, Senegalese wrestling combines professional athleticism with cultural traditions, political relations, and religious belief. For many young men in Senegal, wrestling also represents a model of success in otherwise challenging circumstances characterized by socio-economic crisis and increasing precarity. Young wrestlers must navigate and perform an elaborate set of identities in order to demonstrate their success—both within the sand-filled arenas in which fights take place, and in the complex social worlds which have emerged around the practice. Referring to a panoply of identity markers including ethnicity, religious affiliation, and village or neighborhood loyalty, wrestlers simultaneously demonstrate their alignment with dominant discourses around masculinity and urban knowledge. The article draws upon lengthy ethnographic research to explore the dynamic, contradictory, and hybrid processes of identity construction through which wrestlers present themselves to the world.